Pengembangan Arduino Code Builder Pada Sistem Simulator Smart Home Dengan Rule Terdistribusi - Hery Julianto Situmorang; Edita Rosana Widasari; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Nowadays, there are numbers of researches on Smart Home that have been done by technicians even though they need a lot of relevant hardware and periods of time to design plan and ways of implementation for the Smart Home. Therefore, this research conducted with focus on developing Smart Home simulator based on desktop application which can improve the time and hardware needed since it enables the Smart Home to be used without utilizing lots of hardware. The system consists of two applications which are (i) Control and Monitoring application and (ii) Object Simulator application. The Control and Monitoring application provides user's information, list of object and information of rule. In this system, the method of distributed rule will be implemented to turn on and turn off the objects while the objects for this present research are PIR sensor and lamps. Rule contains patterns for which lamps that are going to on if the PIR sensor detects the human existence. This system also produces program code for PIR sensor and light nodes that aim to validate the use of distributed rules on hardware. The result of this research shows that simulator object can receive rule from Control and Monitoring application with the success rate of 100% out of 28 times rule transmissions and also can be executed with the success rate of 100% out of 28 times tests. The application can also display the program code according to the rule chosen by the user.